Patch-Recovery Filters for Curvature in Discontinuous Galerkin-Based Level-Set Methods (Communications in Computational Physics, 2018)
In two-phase flow simulations, a difficult issue is usually the treatment ofsurface tension effects. These cause a pressure jump that is proportional to the curvatureof the interface separating the two fluids. Since the evaluation of the curvature incorporatessecond derivatives, it is prone to numerical instabilities. Within this work,the interface is described by a level-set method based on a discontinuous Galerkindiscretization. In order to stabilize the evaluation of the curvature, a patch-recoveryoperation is employed. There are numerous ways in which this filtering operationcan be applied in the whole process of curvature computation. Therefore, an extensivenumerical study is performed to identify optimal settings for the patch-recoveryoperations with respect to computational cost and accuracy.